2013
DOI: 10.3109/13880209.2013.801995
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Japanese traditional herbal medicines (Kampo) on growth and virulence properties ofPorphyromonas gingivalisand viability of oral epithelial cells

Abstract: Results: Of the 27 Kampos tested, 7 were found to inhibit the growth of P. gingivalis. The lowest minimal inhibitory concentration (MIC) (250 mg/ml) was obtained with TJ-113. Analysis of the composition of the seven active Kampos showed that they contain Chinese rhubarb as a common ingredient. Therefore, additional growth inhibitory assays on P. gingivalis were carried out with purified anthraquinones known to be present in rhubarb. Aloe-emodin and rhein possessed the strongest antibacterial effects towards P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…These effects mainly have biological effects against host cells. As clinical trials using antibiotics and CPC or oriental medicine have reported their bactericidal activities, halitosis may be ameliorated by the suppression of bacterial growth (Liao et al , ). However, the concentration used in this study did not show any antibacterial effects against Pg .…”
Section: Discussionmentioning
confidence: 99%
“…These effects mainly have biological effects against host cells. As clinical trials using antibiotics and CPC or oriental medicine have reported their bactericidal activities, halitosis may be ameliorated by the suppression of bacterial growth (Liao et al , ). However, the concentration used in this study did not show any antibacterial effects against Pg .…”
Section: Discussionmentioning
confidence: 99%
“…These mainly comprise emodin, rhein, chrysophanol, aloe-emodin, and physcion (Lin et al, 2008; Wierzchacz et al, 2009). Rhein can impair the pathogenicity of Porphyromonas gingivalis pathogenicity by intervening in the transcription of genes, these genes code important virulence factors which affect the bacterial proteolytic activity of the bacterium (Liao et al, 2013). Aloe-emodin can disrupt bacterial membranes by interposing between the two major phospholipids (phosphatidylethanolamine and phosphatidylglycerol) (Liao et al, 2013) that are present in bacterial membranes.…”
Section: Introductionmentioning
confidence: 99%
“…However, little research has been conducted on their potential beneficial effects on oral health. In a previous study, we investigated the effects of 27 Kampo formulations on the growth and virulence properties of Porphyromonas gingivalis ( P. gingivalis ), which is a major pathogen of chronic periodontitis and showed that Kampo formulations containing Rhubarb Rhizome (Daio), including Daiokanzoto (TJ-84), can decrease the growth of P. gingivalis and its adherence to oral epithelial cells, suggesting that they may have potential for preventing periodontal diseases [2]. Moreover, in vitro evidence has shown that some Kampo formulations can decrease inflammation and bacterial infections of oral mucosa.…”
Section: Introductionmentioning
confidence: 99%